Treatment of Waldenstrom's macroglobulinemia - Dimopoulos, M.A.; Anagnostopoulos, A. (Current Treatment Options in Oncology, 2007)
Waldenstrom's macroglobulinemia is defined by bone marrow lymphoplasmacytic infiltration and by production of monoclonal IgM. Treatment is employed only to symptomatic patients. Alkylating agents (chlorambucil), nucleoside analogues and rituximab are reasonable choices for primary therapy. Combination therapy either with nucleoside analogues with alkylating agents and/or rituximab or rituximab with chemotherapy such as CHOP or cyclophosphamide are also reasonable frontline treatment options for WM patients. Several factors should be taken into account when choosing the most appropriate primary treatment. These factors include the age of the patient and possible co-morbidities, the presence of cytopenias and especially thrombocytopenia, the presence of symptoms and signs indicative of hyperviscosity, the need for rapid disease control due to severe symptoms, significant splenomegaly or lymphadenopathy, symptomatic peripheral neuropathy and whether the patient is candidate for autologous stem cell transplantation. For patients with refractory or relapsing disease, the use of an alternate first-line agent is reasonable. Outside the setting of a clinical trial, the administration of high-dose therapy should be reserved only for patients refractory to alkylating agents, purine nucleoside and rituximab. For patients who develop resistance to all three classes of agents, alemtuzumab, thalidomide with or without dexamethasone or bortezomib could be tried. © Springer Science+Business Media, LLC 2007.